Linking biopsychosocial indicators with financial risk tolerance and satisfaction through macroeconomic literacy: A structural equation modeling approach - Muhammad Hasnain Abbas Naqvi; Yushi Jiang; Miao Miao; Mishal Hasnain Naqvi (Cogent Economics & Finance, 2020)
The purpose of the current research was to analyze the impact of biopsychosocial indicators on the financial risk tolerance (FRT) and financial satisfaction along with the mediating role of macroeconomic literacy in these associations. For this purpose, three indicators names as "personality type, self-esteem, and sensation seeking" were used to check the impact of biopsychosocial indicators on FRT and financial satisfaction. The current study was conducted in China where the data was collected from retail investors through structured questionnaire. The purposive sampling technique was used to decide the sample from the population. The data were collected from 1134 retail investors and SPSS and AMOS were used to analyze the data by applying SEM. Findings of the current study revealed that the personality, self-esteem and sensation seeking have significant influences on FRT. It has been further found that the personality type and self-esteem have significant influences on the financial satisfaction. Results further confirmed the mediating role of macroeconomic literacy between self-esteem and FRT, personality type and FRT, self-esteem and financial satisfaction, and personality type and financial satisfaction. However, no significant mediating role of macroeconomic literacy was found between sensation seeking and FRT, and sensation seeking and financial satisfaction. The current study and findings will be of great importance for theory and practice regarding financial/investment decision making and FRT.
Keywords: 330; biopsychosocial indicators; financial risk tolerance; financial satisfaction; macroeconomic literacy